Влияние свойств металла-катализатора в алмазных зернах на напряженно-деформированное состояние алмазоносного слоя на этапе изготовления инструмента - Федорович, Владимир Алексеевич; Островерх, Евгений Владимирович; Козакова, Наталия Витальевна; Бабенко, Евгений Александрович (Национальный технический университет "Харьковский политехнический институт", 2019)
Приведены результаты 3D моделирования методом конечных элементов процесса спекания комплексной системы «связка–алмазное зерно–металлофаза». Впервые при исследовании процесса спекания расчетным методом установлено влияние физико-механических свойств металлофазы, а также ее процентного содержания в алмазном зерне на напряженно-деформированное состояние данной системы. Установлены наиболее термостойкие виды сплавов-растворителей: Cо–Cr, Ni–Fe–Cr, Fe–Co–Cr, которые обеспечивают целостность зерен на этапе изготовления (спекания) алмазных кругов на керамических связках за счет уменьшения значения приведенных напряжений в системе в 1,7…2,1 раза. Изучение влияния физико-механических свойств металла-катализатора (сплава-растворителя) на напряженно-деформированное состояние исследуемой системы позволяет определить их рациональные значения для различных марок алмаза, что может иметь практическую ценность при синтезе алмаза.

One of the most significant factors affecting the heat resistance of a synthetic diamond is the presence of metallic inclusions in it, which are inevitably present after its synthesis and lead to an increase in internal pressures in the crystal, the appearance of a network of microcracks and metallophase migration on its surface during heating. Taking into account the high temperature load experienced by the diamond layer during sintering of grinding wheels, it becomes necessary to study the effect of the physical properties of the solvent-alloy (metal phase) on the change in the stress-strain state of the binder – diamond grain – metal phase system. The results of 3D modeling by the finite element method of sintering the complex system “bond – diamond grain – metal phase” allow predicting its behavior ensuring the integrity of the diamond grains during the manufacture of an abrasive tool. The influence of the physicomechanical properties of the metal phase, as well as its percentage in the diamond grain, on the stress-strain state of the “binder – diamond grain – metal phase” system has been established for the first time while studying the sintering process. The most heat-resistant types of alloys-solvents were established: Co – Cr, Ni – Fe – Cr, Fe – Co – Cr, which ensure the integrity of the grains at the stage of manufacturing (sintering) diamond circles on ceramic bonds by reducing the value of reduced stresses in the system in 1, 7 ... 2.1 times. Studying the effect of the physicomechanical properties of the metal-catalyst (alloy-solvent) on the stress-strain state of the system under study allows determining their rational values for various grades of diamond, which may be of practical value in the synthesis of diamond.
Influence of properties of metal-catalyst in diamond grains on stressed-deformed state of the diamond-layer on the stage of manufacturing the tool
Keywords: металлофаза; керамическая связка; термостойкие сплавы-растворители; metal phase; ceramic bundle; heat-resistant solvent alloys